A new model system identifies epidermal growth factor receptor–human epidermal growth factor receptor 2 (HER2) and HER2–human epidermal growth factor receptor 3 heterodimers as potent inducers of oesophageal epithelial cell invasion. Issue 4 (5th November 2017) - Fichter, Christiane Daniela; Przypadlo, Camilla Maria; Buck, Achim; Herbener, Nicola; Riedel, Bianca; Schäfer, Luisa; Nakagawa, Hiroshi; Walch, Axel; Reinheckel, Thomas; Werner, Martin; Lassmann, Silke
Abstract: Oesophageal squamous cell carcinomas and oesophageal adenocarcinomas show distinct patterns of ErbB expression and dimers. The functional effects of specific ErbB homodimers or heterodimers on oesophageal (cancer) cell behaviour, particularly invasion during early carcinogenesis, remain unknown. Here, a new cellular model system for controlled activation of epidermal growth factor receptor (EGFR) or human epidermal growth factor receptor 2 (HER2) and EGFR–HER2 or HER2–human epidermal growth factor receptor 3 (HER3) homodimers and heterodimers was studied in non‐neoplastic squamous oesophageal epithelial Het‐1A cells. EGFR, HER2 and HER3 intracellular domains (ICDs) were fused to dimerization domains (DmrA/DmrA and DmrC), and transduced into Het‐1A cells lacking ErbB expression. Dimerization of EGFR, HER2 or EGFR–HER2 and HER2–HER3 ICDs was induced by synthetic ligands (A/A or A/C dimerizers). This was accompanied by phosphorylation of the respective EGFR, HER2 and HER3 ICDs and activation of distinct downstream signalling pathways, such as phospholipase Cγ1, Akt, STAT and Src family kinases. Phenotypically, ErbB dimers caused cell rounding and non‐apoptotic blebbing, specifically in EGFR–HER2 and HER2–HER3 heterodimer cells. In a Transwell assay, cell migration velocity was elevated in HER2 dimer cells as compared with empty vector cells. In addition, HER2 dimer cells showed in increased cell invasion, reaching significance for induced HER2–HER3 heterodimers ( P  = 0.015). Importantly, in three‐dimensional organotypic cultures, empty vector cells grew as a superficial cell layer, resembling oesophageal squamous epithelium. In contrast, induced HER2 homodimer cells were highly invasive into the matrix and formed cell clusters. This was associated with partial loss of cytokeratin 7 (when HER2 homodimers were modelled) and p63 (when EGFR–HER2 heterodimers were modelled), which suggests a change or loss of squamous cell differentiation. Controlled activation of specific EGFR, HER2 and HER3 homodimers and heterodimers caused oesophageal squamous epithelial cell migration and/or invasion, especially in a three‐dimensional microenvironment, thereby functionally identifying ErbB homodimers and heterodimers as important drivers of oesophageal carcinogenesis. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.